Longitudinal relationship between wheelchair exercise capacity and life satisfaction in patients with spinal cord injury: A cohort study in the Netherlands. (May 2014) - van Koppenhagen, Casper Floris; Post, Marcel; de Groot, Sonja; van Leeuwen, Christel; van Asbeck, Floris; Stolwijk-Swüste, Janneke; van der Woude, Lucas; Lindeman, Eline
<x content-type="archive" xml:space="preserve">Abstract</x> Objective To examine the relationship between wheelchair exercise capacity and life satisfaction in persons with spinal cord injury from the start of active inpatient rehabilitation up to 5 years after discharge. Design Prospective cohort study. Subjects Persons with spinal cord injury, aged 18–65 years, and wheelchair dependent at least for long distances. Method Measurements at the start of active rehabilitation, after 3 months, at discharge from inpatient rehabilitation, and 1 and 5 years after discharge. A peak wheelchair exercise test was performed to record peak oxygen uptake (VO2peak) and peak power output (POpeak). Life satisfaction was measured as current life satisfaction and change of life satisfaction in comparison with life after spinal cord injury. Relationships between (changes in) exercise capacity and (changes in) life satisfaction were analyzed random coefficient analysis, corrected for possible confounders (age, gender, level of lesion, functional status, secondary impairments, pain, and sports activity) if necessary. Results Of 225 persons included, 130 attended two or more peak exercise tests, who were include in the analyses. Mean age at start was 39 years, 75% were male, 73% had paraplegia, and 76% had a traumatic lesion. Mean POpeak increased during the study from 32.9 to 55.9 Watts, mean VO2peak from 1.02 to 1.38 l/minute, and mean life satisfaction from 5.7 to 7.8. An increase of POpeak with 10 W was associated with a 0.3-point increase of life satisfaction (P = 0.01). An increase of VO2peak with 0.1 l/minute was associated with a 0.1-point increase of life satisfaction (P = 0.049). Conclusion High(er) wheelchair exercise capacity is related to high(er) life satisfaction in spinal cord injury patients.